On the classification of duality defects in c = 2 compact boson CFTs with a discrete group orbifold - Yuma Furuta (Journal of High Energy Physics)
Abstract We propose a novel approach to exploring duality defects in the c = 2 compact boson conformal field theory (CFT). This study is motivated by the desire to classify categorical symmetries, particularly duality defects, in CFTs. While the c = 1 case has been extensively studied, and the types of realizable duality defects are largely understood, the situation becomes significantly more complex for c = 2. The simplicity of the c = 1 case arises from the fact that its theory is essentially determined by the radius of compactification. In contrast, the c = 2 case involves more parameters, leading to a more intricate action of T-duality. As a result, directly solving the condition for a theory to be self-dual under orbifolding becomes highly challenging. To address this, we categorize duality defects into four types and demonstrate that the condition for a toroidal branch theory to be self-dual under an orbifold induced by an automorphism generated by shift symmetry can be reformulated as quadratic equations. We also found that for “almost all” theories we can enumerate all solutions for such equations. Moreover, this reformulation enables the simultaneous exploration of multiple duality defects and provides evidence for the existence of duality defects under specific parameter families for the theory, such as (τ, ρ) = (it, 1 2 $$ \frac{1}{2} $$ + it) where t ∈ ℚ.